Analisis Perangkat Pembelajaran Berbasis Higher Order Thinking Skill (HOTS) di Masa Pandemi Covid-19 - Euis Vera Nursari; Ina Setiawati; Lilis Lismaya (ALVEOLI: Jurnal Pendidikan Biologi, 2021)
Higher order thinking skill (HOTS)-based learning tools prepared by teachers are often not optimally prepared in learning activities, especially in online learning, so there are still many teachers who are not optimal in compiling higher order thinking skill (HOTS)-based learning tools. This study aims to analyze (1) the Learning Process Plan (RPP) based on higher order thinking skills (HOTS) during the covid-19 pandemic, (2) the implementation of learning based on higher order thinking skills (HOTS) during the covid-19 pandemic. , (3) evaluation of higher order thinking skill (HOTS) based learning during the covid-19 pandemic. The type of research used is descriptive qualitative. The research subject is a biology teacher in class XI of SMAN 2 Kuningan. The object of research includes lesson plans, implementation of learning, and evaluation of learning. Data collection techniques consist of observation and documentation. Data analysis through credibility test, transferability test, dependability test, and confirmability test. The results of this study indicate that (1) the Learning Process Plan (RPP) is based on higher order thinking skills (HOTS) during the covid-19 pandemic with a good category, (2) the implementation of learning is based on higher order thinking skills (HOTS) during the pandemic. covid-19 with a very good category, (3) the evaluation of learning has been based on higher order thinking skills (HOTS) during the covid-19 pandemic with a good category.  Keywords: Higher Order Thinking Skill (HOTS), learning tools, online learning,  Perangkat pembelajaran berbasis higher order thinking skill (HOTS) yang disusun oleh guru sering kali tidak dipersiapkan secara maksimal dalam kegiatan pembelajaran terutama dalam pembelajaran daring, sehingga masih banyak guru yang belum maksimal dalam menyusun perangkat pembelajaran berbasis higher order thinking skill (HOTS). Penelitian ini bertujuan untuk menganalisis (1) Rencana Proses Pembelajaran (RPP) yang berbasis higher order thinking skill (HOTS) di masa pandemi covid-19, (2) pelaksanaan pembelajaran yang berbasis higher order thinking skill (HOTS) di masa pandemi covid-19, (3) evaluasi pembelajaran berbasis higher order thinking skill (HOTS) di masa pandemi covid-19. Jenis penelitian yang digunakan adalah kualitatif deskriptif. Subjek penelitiannya guru biologi kelas XI SMAN 2 Kuningan. Objek penelitian meliputi RPP, pelaksanaan pembelajaran, dan evaluasi pembelajaran. Teknik pengumpulan data terdiri observasi dan dokumentasi. Analisis data melalui uji credibility, uji transferability, uji dependability, dan uji confirmability. Hasil penelitian ini menunjukkan bahwa (1) Rencana Proses Pembelajaran (RPP) sudah berbasis higher order thinking skill (HOTS) di masa pandemi covid-19 dengan kategori baik, (2) pelaksanaan pembelajaran sudah berbasis higher order thinking skill (HOTS) di masa pandemi covid-19 dengan kategori sangat baik, (3) evaluasi pembelajaran sudah berbasis higher order thinking skill (HOTS) di masa pandemi covid-19 dengan kategori baik. Kata Kunci : Higher Order Thinking Skill, perangkat pembelajaran, pembelajaran daring.